Evaluation of arene ruthenium(II) N-heterocyclic carbene complexes as organometallics interacting with thiol and selenol containing biomolecules - Oehninger, Luciano; Stefanopoulou, Maria; Alborzinia, Hamed; Schur, Julia; Ludewig, Stephanie; Namikawa, Kazuhiko; Muñoz-Castro, Alvaro; Köster, Reinhard W.; Baumann, Knut; Wölfl, Stefan; Sheldrick, William S.; Ott, Ingo (Dalton transactions, 2013)
Metal complexes with N-heterocyclic carbene (NHC) ligands have been widely used in catalytic chemistry and are now increasingly considered for the development of new chemical tools and metal based drugs. Ruthenium complexes of the type (p-cymene)(NHC)RuCl2 interacted with biologically relevant thiols and selenols, which resulted in the inhibition of enzymes such as thioredoxin reductase or cathepsin B. Pronounced antiproliferative effects could be obtained provided that an appropriate cellular uptake was achieved. Inhibition of tumor cell growth was accompanied by a perturbation of metabolic parameters such as cellular respiration.
First published 26 Oct 2012
Gesehen am 06.12.2021